2021
DOI: 10.1108/ebr-11-2020-0306
|View full text |Cite
|
Sign up to set email alerts
|

Extending the theory of planned behaviour to understand the effects of barriers towards sustainable fashion consumption

Abstract: Purpose Extending the theory of planned behaviour (TPB), this paper aims to measure the relative importance of different barriers to sustainable fashion consumption (SFC). Design/methodology/approach Existing studies have mainly adopted a qualitative methodology for identifying barriers to uptake of SFC, this study uses six of the main identified barriers: environmental apparel knowledge, perceived value, price sensitivity, product attributes and variety, availability and scepticism into the TPB framework to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(74 citation statements)
references
References 118 publications
(213 reference statements)
2
48
0
Order By: Relevance
“…Previous studies have identified a number of variables that influence consumers' perceived opportunity for sustainable consumption. Despite the awareness of environmental concerns, consumers tend to focus on price, value, and style in the decision to purchase sustainable clothes [44,45]. Limited retail stores, green alternatives, style, and size options often make purchasing the sustainable apparel challenging for consumers [46].…”
Section: Opportunitymentioning
confidence: 99%
“…Previous studies have identified a number of variables that influence consumers' perceived opportunity for sustainable consumption. Despite the awareness of environmental concerns, consumers tend to focus on price, value, and style in the decision to purchase sustainable clothes [44,45]. Limited retail stores, green alternatives, style, and size options often make purchasing the sustainable apparel challenging for consumers [46].…”
Section: Opportunitymentioning
confidence: 99%
“…Products that are supposedly sustainable (e.g. hybrid cars, energy-saving light bulbs) have been greatly underwhelming, overpriced, inconvenient, ineffective, or unavailable (Brandão & da Costa, 2021;Lim & Weissmann, 2021;Lim et al, 2013;Olson, 2013;Weissmann, 2020;Weissmann & Hock, 2021). More often than not, anticonsumption, green, ethical, and social marketers have tried to prod consumers to act by relying on guilt or by encouraging them to "save the Earth" (Mkono & Hughes, 2020;Nakajima, 2001), neither of which has turned out to be particularly aspirational or appealing.…”
Section: (Re)thinking Sustainabilitymentioning
confidence: 99%
“…The concept of sustainable fashion is anchored on the triple bottom line principle that emphasizes the need to maintain an intricate balance of environmental, economic and social goals (Chandran and Bhattacharya, 2019). Critics of the sustainable fashion movement perceive it as a ploy to maximize profit by using the environment as a selling proposition (McNeill and Moore, 2015;Brandao and Costa, 2021). Moreover, greenwashing concerns have been raised, defined as the act of using unsubstantiated environmental claims to market fashion products (Fernando et al, 2014;Mahsud et al, 2018).…”
Section: Slowing Fast Fashionsustainable Fashion Drivers and Counter ...mentioning
confidence: 99%
“…Critics of sustainable fashion are also concerned with the high premium price which is beyond the reach of many consumers (Ritch, 2015;Brandao and Costa, 2021). For instance, previous studies found that consumers are only willing to pay an average of 10-20 per cent premium on sustainable fashion (Žurga and Forte, 2014;Ciasullo et al, 2017).…”
Section: Slowing Fast Fashionsustainable Fashion Drivers and Counter ...mentioning
confidence: 99%